Erratum - BENDIMERAD, Nahida; BOUMEDIENE, Karima; KHIRI, Zahia; DIDOUH, Nassima; CHERIF ANNTAR, Asmaa; BENAMAR, Ibrahim; ZATLA, Ilyes; MOUSSA BOUDJEMAA, Boumediene (Food Science and Technology, 2024)
***